What can we learn from The Teahouse? Exploring the spoken grammar in a drama text as a resource for teaching spoken conversational Chinese - Jianfei Chen (Journal of the National Council of Less Commonly Taught Languages)
The current study investigates the use of a dramatic text to teach spoken Chinese grammar in casual conversation. By analyzing the language used in The Teahouse (1957), a classic Chinese play, this study identifies features of spoken Chinese grammar with a focus on the distinct structures of functionally motivated casual conversation. Utilizing Cullen and Kuo’s categorization of spoken grammar (2007), the analysis offers a new perspective on spoken Chinese, highlighting the interpersonal nature of casual conversation and its implications for teaching spoken grammar. The findings indicate that The Teahouse can serve as a valuable resource for presenting advanced spoken Chinese to students, providing rich models and contextual knowledge. This suggests that incorporating the play as an authentic source of casual conversation in class may significantly enhance students’ understanding and production of spoken Chinese grammar in a meaningful way.